Increasing Chinese exports and U.S labor market outcomes - Caceres Alegre, Jorge Eduardo (Kansas State University, 2019)
China’s major economic upraise over the last decades has created both positive and negative consequences (economically speaking) for other countries. Perhaps the country who has gotten affected the most by this sudden change of hub for world manufacturing is the U.S. It is well known by both scholars and policy makers that the progressive shrinking the U.S manufacturing sector has experienced over the last 20 years or so is in part a product of China’s astonishingly rapid economic development. This paper touches on the subject of estimating the impact of such rapid economic development (particularly increasing Chinese exports) on U.S labor markets specifically. The purpose of this paper is to exemplify some of the more notable methods used in the economic literature through the last decade to estimate the impact of increasing Chinese exports on U.S labor markets. The first strategy discussed is “The Commuting Zone approach” used by Autor, Dorn, and Hanson (ADH 2013) for estimating the impact of increasing Chinese import penetration by relating changes in labor-market outcomes throughout a specific period of time across US local labor markets to changes in exposure to import competition. The second strategy relies on adding what is known as “Input-Output Linkages”, which is what Autor, Dorn, Hanson, and Price (AADHP 2016) used to estimate the impact of increasing Chinese exports on U.S labor markets depending on the position of industries on the production chain. And finally, the last strategy mentioned in this paper relies on “Accounting for Value-Added Exports” in which Da Silva and Shen (DS 2018) compare the magnitude of Chinese exports on U.S labor markets when considering value-added exports instead of gross exports as well as incorporating input-output linkages like AADHP (2016) did. All three studies find increasing Chinese exports to have a negative effect on U.S labor markets. Even though their specifications for such general claim are slightly different from each other (the last two build up on the specifics provided by ADH 2013). ADH (2013) finds that increasing import penetration of Chinese goods yields negative effects on manufacturing employment as well as non-manufacturing. AADHP (2016) find the same results as ADH (2013), and their further specifications suggest that industries with higher degree of upstreamness are the ones more negatively affected, and that the effect of industries with a high degree of downstreamness is ambiguous. Finally, DS (2018) find the same results as ADH (213) but their further specifications imply that industries with high degree of downstreamness are the ones more negatively affected by increasing Chinese imports, and also that accounting for gross exports (instead of value-added) overstates the negative impact caused by increasing Chinese exports on U.S labor markets. As I move on into the latter sections of this paper, I will explain in greater detail the models and strategies (with their respective results) each study used to reach such conclusions.
Keywords: Exports; Labor; China; U.S; Trade; Outcomes